First report of Bovine Viral Diarrhea Virus antigen from pneumonic cattle in Sudan - Saeed, Intisar Kamil; Ali, Yahia Hassan; Taha, Khalid Mohammed; Mohammed, Nada ElAmin; Nouri, Yasir Mehdi; Mohammed, Baraa Ahmed; Mohammed, Osama Ishag; Elmagbool, Salma Bushra; Elghazali, Fahad (Journal of Advanced Veterinary and Animal Research, 2015)
To explore the expected role of Bovine Viral Diarrhea Virus (BVDV) in pneumonia in cattle, cattle lungs (n=242) showing signs of pneumonia were collected from slaughter houses of three different localities located at Northern, Central and Western Sudan during 20102013. The collected samples were tested for the presence of BVDV antigen using Enzyme-Linked Immunosorbent Assay (ELISA), and Fluorescent Antibody Test (FAT). Twenty six (10.7%) out of 242 samples were found to be positive for BVDV. Positive results were seen in all the three studied areas, with the highest prevalence (16.7%; n=4/24) at Gezira State in Central Sudan. BVDV genome could be detected in all ELISA positive samples. The results indicated the existence of BVDV infection in cattle in different areas in Sudan, and its possible association with respiratory infections in cattle. Analysis using BLAST indicated that the sequence was identical to the previously reported BVDV-1 (GenBank accession AF220247.1.); nucleotide A was found in our study at position 9 of our sequence, whereas T was present instead in the reference virus. This is the first report of detecting BVDV antigen, genome, and its sequence analysis collected from cattle lungs in Sudan. http://dx.doi.org/10.5455/javar.2015.b67